Pemberdayaan pada Penderita Diabetes Tipe 2 dan Kader Kesehatan dalam Pelaksanaan Program Pos Binaan Terpadu Penyakit Tidak Menular (Posbindu PTM) - Arief Andriyanto; Etty Rekawati; Dwi Cahya Rahmadiyah (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2020)
Diabetes mellitus is classified as a non-communicable disease which has been estimated to have increased, so a risk factor control program recommended by the Ministry of Health is required according to the DM management pillar. Health cadre empowerment is also needed to actively support non-communicable diseases programs. The purpose of this community empowerment was to change the behaviour of people with type 2 diabetes in glucose control and improve the health cadres' skills in Posbindu PTM activities. The program was carried out in October 2018 until March 2019. The targets were: 86 type 2 diabetes patients, 24 cadres in Cisalak Pasar Kelurahan, 120 cadres in Cimanggis District, and 293 cadres in Depok City. The results showed that patients could control their glucose and health cadres experienced improved skills. The role of community nurses is continuously needed to provide appropriate interventions to the patients.